Adult female mule deer global positioning system radio collar data from the Piceance Basin, CO, USA, 2008 – 2010 - Northrup, Joe; Anderson, Chuck (Colorado State University. Libraries, 2016)
These data represent GPS radio collar data from adult female mule deer (> 1 year old) on their winter range in the Piceance Basin in NW Colorado. The data are from 54 unique individuals fit with collars set to attempt a relocation once every 5 hours. As data represent the precise locations of a hunted species, the locations are relative locations: a constant value has been subtracted from each location. The original projection of the data is NAD 1983 UTM Zone 12N.
Data were collected from January 2008 through May 2010.
Department of Fish, Wildlife, and Conservation Biology